Transtheoretical Model Based Exercise Counseling Combined with Music Skipping Rope Exercise on Childhood Obesity - Ok Kyung Ham, RN, PhD, MCHES; Kyung Mi Sung, RN, PhD; Bo Gyeong Lee, RN, MS; Hee Won Choi, BS, RN; Eun-Ok Im, PhD, MPH, FAAN (Elsevier, 2016)
Purpose: The purpose was to evaluate the effects of a transtheoretical model (TTM) based exercise counseling offered with music skipping rope exercise on components of the TTM (stages of change, decisional balance, and self-efficacy), body mass index, glucose, and lipid profile of overweight/obese children in Korea. Methods: This study used a nonequivalent pretest and posttest experimental study design. A total of 75 overweight/obese children participated in the study. Eight sessions of exercise counseling combined with music skipping rope exercise for 12 weeks were offered for children in the experimental group, while one session of exercise counseling with music skipping rope exercise for 12 weeks was offered for children in the control group. Outcomes were measured at baseline, and 6 months after the intervention. Results: After the intervention, self-efficacy significantly improved among children in the experimental group (p = .049), while these children maintained their baseline BMI at 6-month follow-up (p > .05). Among children in the control group, BMI significantly increased (p < .05). Fasting blood sugar significantly increased for both groups after the intervention (p < .05). However, a greater increase was observed for the control group. Conclusions: Our study partially supports the hypothesis that a TTM-based exercise intervention is effective in maintaining BMI and improving self-efficacy of overweight/obese children. The TTM-based counseling combined with exercise classes has potential to control weight among overweight/obese children, while involvement of parents and children in the development of the theory-based intervention may generate further benefits regarding health and well-being of overweight/obese children.